The neonatal Fc receptor expression during macrophage differentiation is related to autophagy - Lamamy, Juliette; Larue, Anthony; Mariot, Julie; Dhommée, Christine; Demattei, Marie-Véronique; Delneste, Yves; Gouilleux-Gruart, Valérie (Frontiers in Immunology, 2022)
The neonatal Fc receptor (FcRn) plays a central role in recycling and biodistributing immunoglobulin G. FcRn is also involved in many physiological immune functions as well as pathological immune responses in cancer or autoimmune diseases. Low levels of FcRn in tumor cells and the microenvironment is associated with poor prognosis in non-small cell lung cancers. Among cells that are present in the tumor microenvironment, macrophages express high levels of FcRn. Macrophages are involved in these pathophysiological contexts by their dual differentiation states of pro- or anti-inflammatory macrophages. However, variations in FcRn protein expression have not been described in macrophage subtypes. In this work, we studied FcRn expression in an in vitro model of pro- and anti-inflammatory macrophage differentiation. We demonstrated an inverse relation between FcRn protein and mRNA expression in macrophage populations. Autophagy, which is involved in protein degradation and acquisition of phagocytic function in macrophages, participated in regulating FcRn levels. Intravenous immunoglobulin protected FcRn against autophagosome degradation in anti-inflammatory macrophages. Our data demonstrate that autophagy participates in regulating FcRn expression in pro- and anti-inflammatory macrophages. This finding raises new questions concerning the regulation of FcRn in immune functions.